Nitrogen supply in combination of nitrate and ammonium enhances harnessing of elevated atmospheric CO2 through improved nitrogen and carbon metabolism in wheat (Triticum aestivum) - Asif, Muhammad; Zora, Seray; Ceylan, Yasemin; Rehman, Raheela; Ozturk, Levent (CSIRO PUBLISHING, 2020)
Elevated carbon dioxide (e-CO2) levels from ambient (a-CO2) enhance plant biomass production and yield. However, this response is highly dependent on the availability and possibly the form of nitrogen (N) supply to plants. This study aimed to investigate changes in C and N metabolism of wheat (Triticum aestivum L.) in response to e-CO2 and N source. e-CO2 enhanced net CO2 assimilation but at highly variable rates depending on the form of N supply. Under e-CO2, net CO2 assimilation rate was in the order NO3- > NH4NO3 > NH4+ > urea. Plants supplied with ammonium and nitrate (i.e. NH4NO3) performed better in terms of biomass production and expressed a higher biomass enhancement ratio by e-CO2 than plants receiving sole applications of NO3-, NH4+ or urea. Supply of NH4NO3 also resulted in lower intercellular CO2, higher photoassimilate translocation to roots and lower accumulation of free amino acids than other N forms, indicating a better exploitation of the e-CO2 environment. Our results conclude that major physiological pathways of photosynthesis and protein and carbohydrate metabolism are differentially influenced by e-CO2 depending on the source of N supply. A balanced supply of NO3- and NH4+ to plant roots is the key to harnessing e-CO2 while minimising its adverse effects on quality of the produce.
Keywords: climate change; crop productivity; nitrogen form; nutritional quality; WINTER-WHEAT; GRAIN-YIELD; PHOTOSYNTHESIS; GROWTH; ENRICHMENT; DIOXIDE; ASSIMILATION; NUTRITION; RESPONSES; MAIZE; Agriculture